2003
DOI: 10.1002/oti.185
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of psychosocial occupational therapy in a life‐story perspective. a long‐term follow‐up of three cases

Abstract: This study is a long-term follow-up in narrative form of three former psychiatric patients who had been discharged eight to nine years earlier from an outpatient occupational therapy programme. The purpose of the study was to gain an understanding about the participants' views about the period of therapy from a long-term perspective and of how the outcome of therapy could be understood within the context of the patients' life plots. In-depth retrospective interviews and two former interviews with each particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, by using creative activities clients could find alternative strategies to master challenges in their life (e.g., la Cour, Josephsson, Tishelman & Nyg ard, 2007). In addition, Eklund, Rottpeter and Vikstr€ om (2003) found that even in a long-term perspective, the use of creative activities had served as a starting point for reflections concerning a client's life situation. Peruzza and Kinsella found in their review that only four of the 19 studies were based on a quantitative design.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using creative activities clients could find alternative strategies to master challenges in their life (e.g., la Cour, Josephsson, Tishelman & Nyg ard, 2007). In addition, Eklund, Rottpeter and Vikstr€ om (2003) found that even in a long-term perspective, the use of creative activities had served as a starting point for reflections concerning a client's life situation. Peruzza and Kinsella found in their review that only four of the 19 studies were based on a quantitative design.…”
Section: Introductionmentioning
confidence: 99%
“…The life story programme, which has great occupational therapy potential, requires sensitivity and trust. Building a trusting relationship with a person is particularly relevant when proposing use of the content of resident's life stories (Eklund et al, 2003) to creatively and sensitively construct an individual reality within a residential facility. This requires appropriately trained and informed facilitators who have the ability to transform the autobiographical narratives of residents into environmental, occupational, sensory and psychosocial manifestations of their lives (Jackson, 1996).…”
Section: Implications For Occupational Therapymentioning
confidence: 99%
“…For occupational therapists, the need for recognition and understanding of the dynamics of occupational reminiscence as a powerful intervention within this population is important. Insight and understanding of their stories will assist in the provision of meaningful and purposeful occupational intervention (Eklund et al, 2003) to enhance the quality of life of aging migrants in care.…”
Section: Introductionmentioning
confidence: 99%
“…I hope that it does find a home in occupational therapy because there are various similarities that indicate that it is a good fit for this field. For example, occupational therapy has defined itself as a field that uses narrative to develop theory and practice (Clark 1993, Helfrich et al 1994, Burke and Kern 1996, Larson and Fanchiang 1996, Price-Lackey and Cashman 1996, Clark et al 1997, Mattingly and Lawlor 2000, Clouston 2003, Eklund et al 2003, Wicks and Whiteford 2003, Finlay 2004, Gahnstrom-Strandqvist et al 2004 and also has diverse theories to explain occupational behaviour. It is comfortable with case method and the search to understand rather than predict.…”
Section: Psychobiography and Occupational Therapy: A Good Matchmentioning
confidence: 99%